Development of multifunctional different cross-sectional shaped coaxial composite filaments for SMART textile applications. Issue 16 (October 2017) - Afzal, Ali; Drean, Jean-Yves; Harzallah, Omar; Khenoussi, Nabyl; Ahmad, Sheraz; Akhtar, Niaz-Ahmad
The aim of this study is to design a spinneret that can be used efficiently for the manufacturing of coaxial composite filaments. Poly(ethylene terephthalate) was used as resin matrix with 99.9% pure copper filament as the core. The characterization of the polymer was done to determine polymer thermal and rheological properties. Multi-shaped coaxial composite filaments were obtained after successful laboratory-scale melt extrusion machine modification and spinneret development. The cross-sectional surface and shape were analyzed with a scanning electron microscope. Coaxial filaments having the cross-section including elliptical, triangular, rectangular and circular shapes were developed. The characterization of spinneret design and coaxial composite filaments were also reported. The effect of spinneret design parameters on the cross-sectional shape of the filament were analyzed.